Development of a nursing intervention to prepare frail older patients for cardiac surgery (the PREDOCS programme), following phase one of the guidelines of the Medical Research Council. (1st December 2014) - Ettema, Roelof G A; Hoogendoorn, Marga E; Kalkman, Cor J; Schuurmans, Marieke J
Abstract: Background: In older patients undergoing elective cardiac surgery, the timely identification and preparation of patients at risk for frequent postoperative hospital complications provide opportunities to reduce the risk of these complications. Aims: We developed an evidence-based, multi-component nursing intervention (Prevention of Decline in Older Cardiac Surgery Patients; the PREDOCS programme) for application in the preadmission period to improve patients' physical and psychosocial condition to reduce their risk of postoperative complications. This paper describes in detail the process used to design and develop this multi-component intervention. Methods: In a team of researchers, experts, cardiac surgeons, registered cardiac surgery nurses, and patients, the revised guidelines for developing and evaluating complex interventions of the Medical Research Council (MRC) were followed, including identifying existing evidence, identifying and developing theory and modelling the process and outcomes. Additionally, the criteria for reporting the development of complex interventions in healthcare (CReDECI) were followed. Results: The intervention is administered during a consultation by the nurse two to four weeks before the surgery procedure. The consultation includes three parts: a general part for all patients, a second part in which patients with an increased risk are identified, and a third part in which selected patients are informed about how to prepare themselves for the hospital admission to reduce their risk. Conclusions: Following the MRC guidelines, an extended, stepwise, multi-method procedure was used to develop the multi-component nursing intervention to prepare older patients for cardiac surgery, creating transparency in the assumed working mechanisms. Additionally, a detailed description of the intervention is provided.